School Sector Differences in Student Achievement in Australian Primary and Secondary Schools: A Longitudinal Analysis - Marks, G; Marks, Gary (My University, 2015)
This article examines school sector differences in student performance Years 3, 5, and 7 in numeracy, reading, writing, spelling and grammar using data from the Longitudinal Study of Australian Children and the national testing program (NAPLAN). At each of the 3 Year levels, there are sizable school sector differences with students from independent schools exhibiting the substantially higher mean scores than Catholic and government school students. However, school sector differences in Years 3 and 5 largely disappear when taking into account students’ socioeconomic position and especially prior ability. In Year 7, there is evidence of value added effects for attending an independent school in numeracy, reading and writing but the effect sizes are quite small (around 0.10). Fixed effects analyses confirm small significant value-added effects for attending independent schools for numeracy and reading.
Keywords: Children -- School age; Education and Training -- Primary; Education and Training -- Educational level; Child Development; Learning, education and training; Childhood and child development; Education and Training; Children; Child Development; School age; Educational level; Primary; Childhood and child development; Learning, education and training